Kleptopredation: a mechanism to facilitate planktivory in a benthic mollusc. (1st November 2017) - Willis, Trevor J.; Berglöf, Kimberly T. L.; McGill, Rona A. R.; Musco, Luigi; Piraino, Stefano; Rumsey, Claire M.; Fernández, Tomás Vega; Badalamenti, Fabio
Abstract : Predation occurs when an organism completely or partially consumes its prey. Partial consumption is typical of herbivores but is also common in some marine microbenthic carnivores that feed on colonial organisms. Associations between nudibranch molluscs and colonial hydroids have long been assumed to be simple predator–prey relationships. Here we show that while the aeolid nudibranch Cratena peregrina does prey directly on the hydranths of Eudendrium racemosum, it is stimulated to feed when hydranths have captured and are handling prey, thus ingesting recently captured plankton along with the hydroid polyp such that plankton form at least half of the nudibranch diet. The nudibranch is thus largely planktivorous, facilitated by use of the hydroid for prey capture. At the scale of the colony this combines predation with kleptoparasitism, a type of competition that involves the theft of already-procured items to form a feeding mode that does not fit into existing classifications, which we term kleptopredation. This strategy of subsidized predation helps explain how obligate-feeding nudibranchs obtain sufficient energy for reproduction from an ephemeral food source.